AKUNTANSI DI LIHAT DARI SUDUT PANDANG FILSAFAT : STUDI LITERATUR - Rahmawati , Menuk; Carmidah; Sukirno (Program Studi Akuntansi Universitas Panca Bhakti, 2021)
Financial information in the form of numbers is not yet fully reliable, this is indicated by the existence of financial scandals involving large companies, such as Enron in America in 2002. This phenomenon is the rationale for finding solutions to help overcome potential financial statement irregularities. This study seeks to review the objectives of accounting as seen from the perception of philosophy as a solution to suppress financial statement irregularities. Using meta-analysis by conducting a scientific study of a number of related literature to find scientific truths that are objective, verifiable and communicated to fulfill their functions, namely making descriptions, explaining, developing theories, making predictions and exercising control. The results of the literature show that the field of accounting science is not perfect, it needs to be tested continuously for change, philosophy can be used in the field of accounting with goals based on service to society (social activities) and the emphasis on human factors is more concerned with reducing the dominance of accounting objectives that appear to take into account consequences arising from the financial statements